Thermodynamic and environmental assessment of different scenarios for the insertion of pyrolysis technology in palm oil biorefineries. (20th March 2020) - Ocampo Batlle, Eric Alberto; Castillo Santiago, York; Venturini, Osvaldo José; Escobar Palacio, José Carlos; Silva Lora, Electo Eduardo; Yepes Maya, Diego Mauricio; Albis Arrieta, Alberto Ricardo
Abstract: The large quantities of residual biomass produced in the palm oil industry have become one of the main environmental and financial concerns of this industry. For this reason, biorefineries are gaining strength in recent years, since through their production model the residual biomass can be used as raw material to produce bioenergetics (biofuels and bio-products), hence contributing to the reduction of greenhouse gases emissions. Therefore, the main objective of this work is to compare and evaluate alternatives to convert a conventional palm oil mill into a biorefinery considering energy and environmental sustainability indicators. In this context, this work presents a study of three scenarios: the first (I), the base case, consists of a traditional palm oil mill; the second (II) considers a palm oil mill working under the biorefinery concept that uses the fast pyrolysis process for the production of bio-oil and biochar; and the third (III) considers a biorefinery that, besides incorporating the pyrolysis process, has an extraction/transesterification stage for the production of biodiesel and glycerin in the palm oil mill. The surplus electricity index was calculated for the three scenarios, and scenario III was the most favorable, achieving 110.23 kW per ton of fresh fruit bunch with an overall efficiency of 82.69%. The environmental assessment carried out for scenario III indicates that environmental impacts of bio-oil production are 32.5% lower than the ones to produce electricity (climate change category) and 14.2% lower than environmental impacts to produce biodiesel (resources category), demonstrating that the production of bio-oil using fast pyrolysis result in lower environmental impacts compared with the other products obtained in the biorefinery. Finally, the Net Energy Ratio was calculated for the scenario with the best thermodynamic performance (scenario III: 21.17) and compared with previously published studies, resulting in a gain of total energy flow of up to 17.77. Highlights: Brazil can be considered a potential crude palm oil producer, due to the 7 million hectares available to grow this crop. The scenario with the simultaneous production of bio-oil, biodiesel and electricity has the best electricity surplus index. Production of bio-oil had a lower environmental impact than the production of electricity and biodiesel in some categories. Bio-oil reduces the greenhouse gases emissions due to the carbon neutrality of the biomass.